Perencanaan Kurikulum Muatan Lokal Berbasis Ekologi - Sadiyah, Sadiyah; H Soro, Suharyanto (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the planning of a local content curriculum based on ecology at SMP Ekologi Kahuripan Padjajaran, as well as its integration with Pancawaluya Character Education, the Adiwiyata program, and edukotourism. The study employed a qualitative approach with a descriptive method, involving interviews, observations, and documentation as the main instruments. Data were analyzed thematically to describe the planning process, implementation, and the strengthening of students’ character and ecological awareness. The results indicate that the curriculum utilizes the school’s environmental and cultural potential, making the learning materials contextual and practical. The learning modules are combined with hands-on activities and field projects, enabling students to internalize ecological principles and develop social skills. Pancawaluya Character Education is implemented to foster wisdom, discipline, social care, ecological responsibility, and student cooperation. The Adiwiyata program and edukotourism support direct learning experiences, enhance ecological understanding, and increase student participation. These findings emphasize that the integration of local content, character education, and field practices creates a holistic, practical, and contextually relevant learning experience.